Resource recovery from waste streams for production of microalgae biomass: A sustainable approach towards high-value biorefineries. (June 2022) - Premaratne, Malith; Nishshanka, Gannoru Kankanamalage Sanuji Hasara; Anthonio, Randeniya Arachchige Don Praveen; Liyanaarachchi, Vinoj Chamilka; Thevarajah, Bavatharny; Nimarshana, P.H.V.; Malik, Anushree; Ariyadasa, Thilini U.
Abstract: Microalgae biomass is a robust feedstock which can be utilized for production numerous bioproducts. Nonetheless, their commercialization is hindered by intense costs associated with supplying nutrients required for microalgal growth. Furthermore, supplying nutrients for large-scale microalgal growth is unsustainable due to the depletion of abiotic resources. Thus, researchers have attempted to recover bioavailable nutrients from waste streams such as wastewater, flue gas, and solid waste to enhance the sustainability and economics of microalgae cultivation, while simultaneously performing bioremediation. Nonetheless, current research primarily focuses on employing the generated biomass for low-value applications such as biofuel production. In contrast, the current review delineates a holistic assessment of recovery of nutrients from these numerous waste streams in high-value microalgal biorefineries. Furthermore, strategies which can be employed to address the drawbacks in waste valorization, and future perspectives of this technology are discussed with reference to techno-economic feasibility, life-cycle assessment, public perception, and product safety. Graphical abstract: Unlabelled Image Highlights: Waste resources can be recovered as nutrient sources for microalgae growth. Nutrients can be recovered from wastewater, flue gas, and solid waste. Waste valorization enhances sustainability and economics of biomass production. High-value metabolites can be derived from microalgae grown in waste streams. Numerous hurdles should be overcome to implement waste-integrated biorefineries.